2016
DOI: 10.1002/anie.201605271
|View full text |Cite
|
Sign up to set email alerts
|

Vinylboronic Acids as Fast Reacting, Synthetically Accessible, and Stable Bioorthogonal Reactants in the Carboni–Lindsey Reaction

Abstract: Bioorthogonal reactions are widely used for the chemical modification of biomolecules. The application of vinylboronic acids (VBAs) as non‐strained, synthetically accessible and water‐soluble reaction partners in a bioorthogonal inverse electron‐demand Diels–Alder (iEDDA) reaction with 3,6‐dipyridyl‐s‐tetrazines is described. Depending on the substituents, VBA derivatives give second‐order rate constants up to 27 m −1 s−1 in aqueous environments at room temperature, which is suitable for biological labeling ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 35 publications
(16 reference statements)
2
58
0
2
Order By: Relevance
“…Unstrained alkenes show low reaction rates with tetrazines, although the reaction rate can be enhanced by using electron‐donating substituents . Recently, we reported a large rate enhancement if boronic acid‐substituted alkenes were used instead of their corresponding unsubstituted alkenes in reactions with 3,6‐dipyridyl‐ s ‐tetrazines . These unstrained vinylboronic acids (VBAs) showed, depending on the substituents, second‐order rate constants ( k 2 ) up to 27 m −1 s −1 in 5 % MeOH/phosphate‐buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Unstrained alkenes show low reaction rates with tetrazines, although the reaction rate can be enhanced by using electron‐donating substituents . Recently, we reported a large rate enhancement if boronic acid‐substituted alkenes were used instead of their corresponding unsubstituted alkenes in reactions with 3,6‐dipyridyl‐ s ‐tetrazines . These unstrained vinylboronic acids (VBAs) showed, depending on the substituents, second‐order rate constants ( k 2 ) up to 27 m −1 s −1 in 5 % MeOH/phosphate‐buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…The observed rate constant of VBA ether 6 was lower than expected as we previously observed rate enhancements of up to 100-fold compared to the unsubstituted alkene derivatives. 4 We hypothesize that the moderate rate enhancement is due to the ether on the vinylic position. Since this alcohol is slightly electron-donating, we assume that the alkene becomes more electron-rich, thereby lowering the acidity of the boronic acid, resulting in less favorable coordination to the pyridyl substituents of the tetrazine.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has recently reported a new bioorthogonal tetrazine ligation utilizing vinylboronic acids (VBAs). [4][5][6][7] We showed that by introducing a boronic acid moiety on an alkene, reaction rates of an inverse electron-demand Diels-Alder (iEDDA) reaction with pyridyl-containing tetrazines improved by several orders of magnitude compared to the non-modified linear alkene. 4 The hydrophilic properties and the small size of VBAs compared to other bioorthogonal reactants make them attractive for use in biomolecular labeling experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of a carbamate in allylic position to the double bond of a trans ‐cyclooctene allows for “click‐to‐release” reactions, opening up the possibility for targeted drug delivery . The use of vinylboronic acids can lead to high selectivity towards 2‐pyridyl or 2‐hydroxyphenyl substituted 1,2,4,5‐tetrazines, as recently shown by Bonger and co‐workers. Other bioorthogonal ligations based on aza‐Diels–Alder reactions include the 1,2,4‐triazine ligation introduced by Prescher and co‐workers and a variant of the Kondrat′eva reaction introduced by Jouanno et al.…”
Section: Introductionmentioning
confidence: 89%